Ecosystem of outcome-based contracts : a complex of economic outcomes, availability and performance - Korkeamäki, Lauri; Kohtamäki, Marko (Elsevier, 2019)
The number of studies concerning outcome-based contracts (OBCs) has gradually increased over the past decade, with a focus on servitizing companies. The mutually beneficial baseline logic behind such contracting provides a fascinating area for research because, for instance, it facilitates overcoming the service paradox through network-driven value co-creation. In addition to contractual techniques, the digitization of services in product-service systems (PSS) has gained attention as the enabler of the given business models. We set out to research OBCs that are based on economic value (eOBCs) in the energy technology sector. We mapped the ecosystem surrounding IPP-provider contract relationships and found that the outcomes sold ultimately consist of value propositions made to serve economic outcomes that subsume availability guarantees, which subsequently subsume performance. The depiction of the value system serves as a basis on which to develop future findings concerning practices comprising the outcomes.
Keywords: digital servitization; performance-based contracts; outcome-based contracts; product-service systems (PSS); fi=Johtaminen ja organisaatiot|en=Management and Organization|